Aspektualität in deutschen Partikel- und Präfixverben: Eine kontrastive Untersuchung zu ihrer Polysemie - Stieber, Nana-Lena (Linguistik Online, 2021)
Prefix and particle verbs are part of a systematic way of expressing aspectual structures in German. This article proposes an aspectual analysis of German particle and prefixed verbs, regarding especially their polysemic characteristics, and will give a contrastive comparison with the Italian language. This can be useful given that Italian does not have developed a system of prefixes and particles as German does. Therefore, the Italian translations of German prefixed and particle verbs turns out to use different kinds of expressions, often of a periphrastic nature. This is seen here as an indication in favour of the strongly polysemic verbs in German. The aspectual comparison of both languages will be done using an onomasiological model of aspectuality, which allows the analysis of different kinds of expressions without using specific formal categories. The first part of this article gives a short introduction and definition of the German verbs. Part two concerns the question of what aspectuality in German is, followed by part three, a quick overview of actual research in the field. Part four explains how a contrastive perspective may be helpful to discover and illuminate the polysemic German prefixed and particle verbs. Part five presents the empirical data used for the purpose of this work. Part six, then, contains the aspectual analysis of the German verbs in their given context. Every German example will be described and compared to its Italian translation. The article will close with a quick summary of the results, focussing especially on the usefulness of a contrastive approach.